Classical Urdu Poetry: A Sociological Perspective - Shaista Hameed Khan; Shabnam Niaz (بازیافت)
Abstract: Criticism means the raising of artistic standard of literature. It’s aims at unforlding of incrmenings of interveined with the artistic creations only with throwing light of their different angles and telling this their purpose and importance. Criticism has attained with a place in the contemporary literature that its formal schools of thought have come into existance and social criticism has great importance among them. In modern criticism social criticism is an important method of evaluating and piece of literary creation in the hand of critics. Social criticism is the name of understanding a master literary creation in its background and its analytical evaluation is social criticism. In this article an attempt has been made to throw light on different stages, meanings and importance of social criticism.